KAJIAN INTENSI MAHASISWA BIDANG BISNIS DI KOTA SEMARANG UNTUK MENJADI WIRAUSAHA - Hari Susanta Nugraha (Business UHO: Jurnal Administrasi Bisnis, 2022)
MSMEs are a form of social entrepreneurship that is able to absorb up to 97% of the workforce. This of course can be optimized to reduce the unemployment rate which is a strategic issue from year to year. Unfortunately, this is not offset by the reported entrepreneurship rate of only 3.47%. For this reason, this study aims to analyze the determinants of entrepreneurial intentions in business students in the city of Semarang. This study uses a quantitative approach with data collection techniques using a questionnaire. The primary data in this study is data obtained from the results of a questionnaire, while the secondary data in this study is statistical data collected from various secondary sources. Respondents in this study were 100 business students in the city of Semarang. Data analysis using SEM-PLS with the help of software SmartPLS ver 3.3.2. The results showed that entrepreneurial competence had a significant positive effect on entrepreneurial intentions. On the other hand, attitudes towards entrepreneurial behavior and subjective norms of entrepreneurship have no significant effect on entrepreneurial intentions.